Evaluation of the Geomechanical Properties of Bashkirian Carbonate Rocks at the Tatarstan Republic for Optimization of Hydraulic Fracturing - Ziganshin Eduard; Kolchugin Anton; Dautov Ayrat; Nurieva E. (Russian Journal of Earth Sciences)
Every year, the percentage of development of complex and unconventional hydrocarbon reservoirs is increasing, which is associated with the depletion of traditional oil and gas reserves. Carbonate reservoirs are hard-to-recover reservoir rocks due to the high degree of heterogeneity. A more detailed study of the lithological features and physical properties of carbonate rocks is an important and integral part of the complex reservoirs development. In the present work has done a comprehensive analysis of the lithological and geomechanical properties of the Middle Carboniferous strata deposits of the Dachnoye oil field, located in the southeast of the Republic of Tatarstan. The main attention in the research was focused on the estimation of the britleness of rocks. Britleness index is necessary for correct prediction of hydraulic fracturing. The result of the research is the identification of carbonate facies and their geomechanical characteristics, as well as the estimation of the britleness of rocks by various methods.